Enhancement of Secondary-City Tourism in Phatthalung Province Towards Value Creation using Augmented Reality Technology - Anucharn, Thidapath; Iamchuen, Niti; Jussapalo, Chairat (Burapha Science Journal, 2026)
Emphasis on secondary-city tourism development is important for tourism promotion in Phatthalung. As a result of the novel coronavirus 2019, the tourists cannot travel in different places; thus, the objective of this research is to study the enhancement of secondary-city tourism in order to establish the value with augmented reality technology for online tourist attractions. 10 tourist attractions were selected in terms of Khao (mountain), Pa (forest), Na (field), Le (sea) as models for the development of augmented reality tourism application. This research was addressed into two phases; firstly, tourist attraction data were collected by drone to capture details of various places for construction the 3D model of tourism locations. The flight direction planning was designed by crosshatch with a flight speed of 4 meters per second in north-south direction to avoid shadows. In addition, a 90-degree camera angle was also conducted to capture details on the ground in a vertical angle with 80 percent overlap of the front and sides while the height depended on the surrounding areas. Then, the objects at an oblique angle to capture depth details was taken and the images around the objects were processed every 2 seconds. Finally, the appropriate images were screened and uploaded to the DroneDeploy website for processing the 3D model. The second part is to develop the application of augmented reality technology. The 3D model was imported into Unity3D which the users can select the desired tourist attractions by clicking on the image of the location. Then, the short descriptions of the locations were appeared and moved to attraction menu which users can select 2 modes: 1) AR mode to view 3D model by zoom in and out or rotate the places along with Thai audio description and 2) VDO mode to visualize the surrounding of the places from the bird's eye view of a drone. Therefore, the application is useful for tourists to clearly access tourist information in an online format and is an effective public relation tools to raise awareness of the potential of various places and generate more tourism income in Phatthalung if the novel coronavirus 2019 situation is controlled.